The Changing Identities of American Wives and Mothers - Lafortune, Jeanne; Salisbury, Laura; Siow, Aloysius (Journal of Economic Literature, 2024)
Over the last century, resource allocations within families changed significantly, as did marriage matching patterns. College-educated women became more likely to marry (and, to a lesser extent, have children) than less educated women. A large literature documents these patterns and proposes a variety of explanations. We review this literature. Then, we provide a unified empirical framework, which can integrate these mechanisms. We demonstrate the usefulness of that framework by employing it in decennial US censuses and showing that a combination of technological changes that increased the value of children’s education and enabled more educated women to devote more time to child-rearing are consistent with multiple behavioral changes within marriage, on the marriage market, and before marriage. (JEL I20, J12, J13, J16, N31, N32)